Histopathological Effects of Phytoestrogrn (Genistein) on Thymus Gland of Adult and Post-Natal Female Albino Mice - Ibrahim, Zozan Abdullah; Waheed, Intissar Numman (Science Journal of University of Zakho, 2022)
This study aimed to evaluate how genistein affected the weight and histological structure of the thymus gland in adult and postnatal (P22) female albino mice. Fifteen adult female albino mice and fifteen postnatal (P22) female albino mice were used and divided between two experiments. The animals were divided into three groups (n=5) in each experiment: Group (I), the control group, Group (II), and Group (III), which received 10mg and 50mg genistein/ kg B. W. respectively. In comparison to the control, treatment with 50mg genistein resulted in a significant increase in the weight of the thymus gland in both adult and postnatal mice. When compared to control, treatment with 10mg genistein resulted in a significant increase in this weight in adult females and a significant decrease in the weight of this gland in postnatal mice. Both genistein concentrations had a negative impact on the gland’s histological features. The formation of a "Starry sky" in cortical and medullary regions, an increase in the thickness of regions due to an increase or decrease in the number of T cells depending on genistein concentration, as well as histiocyte hyperplasia and blood vessel congestion, are among these consequences. In conclusion, because genistein affects thymic tissue negatively, it has the potential to create thymic and immunological diseases.